2000
DOI: 10.1093/embo-reports/kvd045
|View full text |Cite
|
Sign up to set email alerts
|

The EXT1/EXT2 tumor suppressors: catalytic activities and role in heparan sulfate biosynthesis

Abstract: The D-glucuronyltransferase and N-acetyl-D-glucosaminyltransferase reactions in heparan sulfate biosynthesis have been associated with two genes, EXT1 and EXT2, which are also implicated in the inherited bone disorder, multiple exostoses. Since the cell systems used to express recombinant EXT proteins synthesize endogenous heparan sulfate, and the EXT proteins tend to associate, it has not been possible to define the functional roles of the individual protein species. We therefore expressed EXT1 and EXT2 in ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
125
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(130 citation statements)
references
References 14 publications
4
125
1
Order By: Relevance
“…As already mentioned, co-expressed EXT1 and EXT2 proteins in mammalian and yeast cells form a hetero-oligomeric complex and colocate to the Golgi apparatus (47)(48)(49), with augmented individual GlcNAc and GlcA transferase activities (49). Nevertheless, in vitro polymerization of a heparan chain remains to be demonstrated.…”
Section: Interactions Between Hs-synthesizing Enzymes To Form Functiomentioning
confidence: 98%
“…As already mentioned, co-expressed EXT1 and EXT2 proteins in mammalian and yeast cells form a hetero-oligomeric complex and colocate to the Golgi apparatus (47)(48)(49), with augmented individual GlcNAc and GlcA transferase activities (49). Nevertheless, in vitro polymerization of a heparan chain remains to be demonstrated.…”
Section: Interactions Between Hs-synthesizing Enzymes To Form Functiomentioning
confidence: 98%
“…Biochemical studies have shown that the vertebrate EXT1 and EXT2 can associate to form biologically functional hetero-oligomeric complex that exhibits glycosyltransferase activity in which both subunits are essential for full activity (Kobayashi et al 2000;McCormick et al 2000;Senay et al 2000;Wei et al 2000;Zak et al 2002). Han et al (2004b) have shown that Ttv and Sotv behave similarly in Drosophila.…”
Section: Ttv Protein Interacts With Hext1mentioning
confidence: 99%
“…A truncated form of human EXT1 (amino acids 29 -746) was amplified by PCR from a previously constructed plasmid (18), with primers 5Ј-ATATGCGGCCGCTAGGGCATCGAGGA-3Ј (forward) and 5Ј-GCCT-GGATCCAAGTCGCTCAATGTCTCG-3 (reverse). All of the PCRs were carried out using the Expand High Fidelity PCR System (Roche Applied Science).…”
Section: Construction Of Expression Plasmids-truncated Forms Of Humanmentioning
confidence: 99%
“…Glycosyltransferase Assays-GlcNAc and GlcA transferase activities were measured essentially as described (18,21) by incubating anti-FLAG agarose-bound enzyme protein preparations with 0.125 Ci of 14 C-labeled UDP sugars (62.5 Ci/ mol; prepared by mixing radiolabeled and unlabeled UDP sugars) and 45 g of oligosaccharide acceptor at 37°C for 2 h. Oligosaccharide acceptors were generated from K5 polysaccharide, as described (22). Labeled products were isolated by gel chromatography and quantified by scintillation counting.…”
Section: Construction Of Expression Plasmids-truncated Forms Of Humanmentioning
confidence: 99%
See 1 more Smart Citation